(untitled) (Bangladesh Journal of Zoology, 2017)
The effects of toxic Microcystis aeruginosa on the liver of Nile tilapia, Oreochromis niloticus were investigated in the laboratory. Four treatments were setup into aquariums for 15 days to investigate the histopathological changes exposed to Microcystis aeruginosa bloom. Fishes of treatment A1 were treated as a control group and given artificial feed. In the three treatments (A2, A3 and A4), the M. aeruginosa cell concentration were 35 × 102, 72 × 102, 149 × 102 colony/ml, respectively. In the control group, no histopathological change was observed. In exposed fish, histopathological alterations were characterized by swollen and granular cytoplasm, vascular proliferation, bile stasis, fatty change and focal necrosis. Histopathological changes were observed within five days of exposure when fish exposed to moderate (72 × 102 colony/ml) to high (149 × 102 colony/ml) bloom concentration, whereas it took 15 days in lower concentration (35 × 102 colony/ml). Histopathological changes proved that intake of toxic M. aeruginosa bloom by aquatic animals, particularly Nile tilapia has significant effects on its internal organs that may cause of massive mortality. Accordingly, cyanotoxin accumulation in fish tissue my pose a risk to human health through the food chain. Bangladesh J. Zool. 45(1): 1-10, 2017